2015
DOI: 10.3109/02770903.2015.1081940
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends and factors associated with pediatric hospitalizations with respiratory infection

Abstract: Objectives Asthma is the leading cause of emergency room visits in children, and those with asthma tend to suffer from more severe consequences of respiratory tract infections. The aims of this study were among children who required hospitalization, compare differences between those admitted with or without respiratory infection, describe changes in yearly proportion of asthma among the children admitted with a respiratory infection in New York City from 2006 to 2012, and ascertain how asthma affected the aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In the present study, short LOS <7 days was significantly associated with asthma. Similarly, Chen et al . reported that the average LOS for those with a respiratory infection was shorter if patients had asthma as compared with patients who did not have asthma.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the present study, short LOS <7 days was significantly associated with asthma. Similarly, Chen et al . reported that the average LOS for those with a respiratory infection was shorter if patients had asthma as compared with patients who did not have asthma.…”
Section: Discussionmentioning
confidence: 94%
“…16 In the present study, short LOS <7 days was Annual percentage change (APC), 5.27%; 95%CI: 1.2-18.1; P < 0.001; ‡ APC, 11.2%; 95%CI: 4.1-18.8; P < 0.001; § APC, 4.8%; 95%CI: À9 to 20.7; P = 0.5; † † APC, À8.8%; 95%CI: À16.6 to À0.2; P < 0.001. significantly associated with asthma. Similarly, Chen et al 17 reported that the average LOS for those with a respiratory infection was shorter if patients had asthma as compared with patients who did not have asthma. RTD are a major cause of hospitalization and have a substantial impact on health-care costs.…”
Section: Discussionmentioning
confidence: 95%
“…Asthma has been reported to increase susceptibility to RTIs, although the mechanisms are poorly understood ( 2 , 3 ). In previous studies, investigators have reported higher risks of both first-time RTIs and recurrent RTIs in persons with asthma than in healthy subjects among several population groups, including children ( 4 13 ), adults ( 14 18 ), hospitalized individuals ( 17 , 19 , 20 ), pregnant women ( 21 ), and smokers ( 14 ). Our previous population-based study showed that atopic diseases, including asthma, rhinitis, and dermatitis, are related to increased risk of RTIs in working-age adults ( 22 ).…”
Section: Abbreviationsmentioning
confidence: 99%
“…There are also differences in the incidence of RTIs and AOM in boys vs. girls. RTIs are reported during the first two years of life with a slightly higher predisposition [ 13 , 22 ] and more frequent hospital visits in boys than in girls [ 23 ]. Being a boy is also considered a risk factor for early AOM or OM [ 15 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%